Multifunctional handheld computers on board merchant vessels - Gyberg, Eva; Wu, Melly (My University, 2014)
This report will discuss possibilities in how to improve and secure information management on board merchant vessels. With the use of a PDA, it can both assist the end user and reduce the steps of information processing. This might be an interesting solution since the crew manning have been reduced while the information rate has increased in combination with extensive regulations. Therefore, this will require convenient methods to compile gathered data for analysis and presentation. With the support from a questionnaire that were addressed to active crewmembers in the profession; the intention was to determine if these people were interested in a PDA as a working tool on board ships. Additionally, if they would prefer to use this kind of equipment, the further goal is to establish what features it should contain and what assignments it can be utilised for. Fundamental conditions were features that are available in some of the existing land based PDAs. When the survey was completed, it was compiled and functions or keywords that were stated a minimum of two times were presented in the results. The results of the survey were then discussed in combination with previously presented facts and findings. Finally, it was concluded that PDAs are interesting as a working tool on board merchant ships, mostly for different types of inspections. This report can be viewed as an introduction to this topic where some features require more studies to become comprehensive.
Keywords: Transport; Annan teknik; Transport; Other Engineering and Technologies